Development of Communicative Skills in the Children with Down’s Syndrome within the Inclusive Education in Preschool Institutions - Tertichna, Nadezhda Anatolievna (Psychological Prospects Journal, 2012)
The article deals with features of the effective communicative skills development of children with Down’s syndrome within the inclusive education in preschool institutions. The experimental psychopedagogic program brought its positive dynamics concerning the level of growth which is observed in communicative skills. Pronounced is the fact that the longer period of time a child with special needs has been visiting an inclusive group the better dynamic we can observe.